ISLAMIC EDUCATION IN THE DIGITAL ERA: AN INTEGRATIVE CONCEPTUAL STUDY OF THE TECH–TOUCH–TEACH PARADIGM - Intania, Naila; Ruwandi, Ruwandi; Saerozi, Saerozi (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
The rapid digital transformation of education presents both opportunities and challenges for Islamic Religious Education (IRE). While technological integration expands access and pedagogical innovation, it also risks ethical disorientation and spiritual detachment if not grounded in Islamic educational philosophy. This study aims to develop an integrative conceptual framework for reconstructing IRE in the digital era through the Tech–Touch–Teach model. Employing a qualitative library research design, this study analyzes classical Islamic educational thought and contemporary digital pedagogy literature to formulate a tauhidic integrative approach. The findings indicate that effective digital transformation in Islamic education must operate dialectically rather than additively: Tech expands epistemic possibilities, Touch ensures spiritual-humanistic depth, and Teach provides pedagogical intentionality. The synthesis of these three dimensions generates a Humanistic-Transcendental Learning Model oriented toward the formation of insan kamil—individuals who are intellectually competent, spiritually grounded, and ethically responsible. The study contributes theoretically by articulating a normative framework that reconciles technological modernity with Islamic educational philosophy, moving beyond technocentric adaptation and traditionalist resistance. Practically, the model implies the need for ethical digital governance, spiritually grounded digital literacy, and holistic assessment systems that integrate cognitive, affective, and moral dimensions. Future empirical research is recommended to validate and operationalize this framework across diverse Islamic educational contexts.